A New Watermarking Method of 3D Mesh Model - Liu Jing; Wang Yinghui; He Wenjuan; Li Ye (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
A new watermarking method for 3D model robust to geometric attacks is presented. The algorithm firstly uses average normal of the part with the obivious geometric feature in the 3D model to establish coordinate system,which is not affected by geometric attacks such as translation,rotation and scaling; Embed the watermarking information into the appropriate vertices selected according to area of 2-ring neighbours of each vertex;Embedding strength adaptively adjusted in terms of curvature of the model facet. The choice of embedding position and the embedding strategy above effectively guarantee good transparency and maximum robustness of the proposed algorithm. Simulation results indicate the ability of  the proposed method to deal with the some attacks more than satisfactory results. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.3853